Clinical Efficacy of Glucagon-like Peptide-1 Receptor Agonists in Patients with Type 2 Diabetes: A Meta-analysis: Clinical Efficacy of GLP-1 RAs in T2DM - Shi, Lei; Meng, Shuai; Ruan, Yuan (Cellular and Molecular Biology, 2023)
Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have been approved to treat type 2 diabetes mellitus (T2DM), which have been considered at the same treatment pattern point as basal insulin (BI). Thus, comprehensively comparing these drugs is conducive to informing the treatment decisions. In this context, this work was developed to evaluate the clinical efficacy and safety of GLP-1 RAs by comparing them with basal insulin. GLP-1 RAs were compared with basal insulin in adults with T2DM with inadequate oral anti-hyperglycemic drug control by searching related literature from MEDLINE, EMBASE, CENTRAL, and PubMed databases, which were published from established the datasets to October 2022. Data on hemoglobin A1c, body weight, and blood glucose were extracted and analyzed. The MD values of HbA1C, weight, and fasting blood glucose (FBG) change were -0.02, -1.37, and -1.68, respectively. Meanwhile, the OR of the hypoglycemia ratio was 0.33. In conclusion, GLP-1 RAs exhibited a great effect on blood glucose and weight control and a better effect on FBG control.